1997
DOI: 10.1007/bf00127409
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic models of myocardial dysfunction

Abstract: Transgenic Technology (TT), is an important tool in the molecular biology arena. It allows one to generate new strains of mice in which a genetic construct is expressed. The construct can be made with a promoter that allows for the targeted expression of a gene of interest to a given part of the cardiovascular system. By so doing, it is possible to modify a given physiologic function and to better understand the structural and functional relationships. This so-called "reverse physiology" is becoming extensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(100 reference statements)
1
3
0
Order By: Relevance
“…We identified two proteins with possible roles in diastolic dysfunction, both of which increased in abundance in stepwise fashion from 4 to 34 months: myosin regulatory light chain 2 (MLC-2) and parvalbumin. It has been reported that MLC-2 overexpression causes diastolic dysfunction (Palermo et al, 1995; Swynghedauw, 1996), thus the upregulation of MLC-2 we observed may play some role in impairing relaxation with age. The upregulation of parvalbumin, however, is most likely adaptive to diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 52%
“…We identified two proteins with possible roles in diastolic dysfunction, both of which increased in abundance in stepwise fashion from 4 to 34 months: myosin regulatory light chain 2 (MLC-2) and parvalbumin. It has been reported that MLC-2 overexpression causes diastolic dysfunction (Palermo et al, 1995; Swynghedauw, 1996), thus the upregulation of MLC-2 we observed may play some role in impairing relaxation with age. The upregulation of parvalbumin, however, is most likely adaptive to diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 52%
“…Of the 46 differentially expressed proteins identified by MALDI-TOF-MS, 16 were associated with the regulation of apoptosis, including parvalbumin, desmin, heat shock protein 27, peroxiredoxin 6, and kallikrein, indicating an adaptive rather than pro-apoptotic alteration. The upregulation of parvalbumin, a calcium binding protein, may also be adaptive to diastolic dysfunction facilitating myocardial relaxation (Schmidt et al, 2005), while the age-related increase in myosin regulatory light chain 2 (MLC-2) potentially contributes to diastolic dysfunction (Swynghedauw, 1996). The age-related increase in the level of 2-oxoglutarate 5 dioxygenase 1 (lysyl hydroxylase 1) may promote the formation of hydroxylysine sites essential for the stability of the intermolecular collagen cross-links, therefore contributing to fibrosis and diastolic dysfunction.…”
Section: Heartmentioning
confidence: 99%
“…For example, the knock-out of the neuronal isoform of nitric oxide (NO) synthase has quite a few consequences in terms of NO production, because of the compensatory expression (or re-expression) of new isoforms [9]. Fifth, transgenic technology has given rise to an incredibly large collection of new animal models, an unexplored treasure for generations of physiologists [6,10]! In addition, these strains are strains of genetically identical animals particularly suitable for physiological and pharmacological research.…”
Section: Are Physiologists Ready For the New Physiology?mentioning
confidence: 98%
“…There are a number of reasons for this. First, because mice are used commonly for transgenic technology, this has generated a lot of physiological investigations on mice, whereby, as we have learnt recently, mice are not small rats [6]! Second, gene transfer or gene knock-out frequently confirms or extends what we know or suspect already.…”
Section: Are Physiologists Ready For the New Physiology?mentioning
confidence: 99%